Effect of Special Kinetics Exercises Pelvic Floor and Bladder Muscles for the Treatment of Urinary Incontinence for the Elderly (60-70) Years - Mashi, Dr. Mushtaq Abed Alredha (International Journal of Psychosocial Rehabilitation, 2020)
A common phenomenon for the elderly is incontinence, which affects both men and women. There has been a long-held belief that no one can do much to reduce or eliminate its effects, but this is no longer true. Significant progress has been made in the treatment of urinary incontinence. New drugs that reduce the signs and symptoms of incontinence are available. Some habits reduce the factors affecting this phenomenon. A number of ideas have emerged to suggest that motor therapy through pelvic floor and bladder exercises significantly contributes to the elimination of this phenomenon, which is, of course, better than chemotherapy or surgical intervention. The aim of this study was to investigate the effect of bladder and pelvic floor muscles for the treatment of urinary incontinence for the elderly (60-70) years. The researchers believe that the motor treatment of the bladder and pelvic floor give good results and contribute to the improvement of the level of health of the injured and develop for the elderly the ability to cope with these psychological stress due to the need to work to get rid of them by self-will of the injured and healthy ways contribute to get rid of this phenomenon. Two groups of elderly males aged (60-70) years were selected. Kinetic exercises were carefully and carefully examined. Clinical examination of the injured was carried out by the specialist in the nursing home in Diwaniya governorate. The results showed an improvement in health status and a clear reduction in the incontinence phenomenon for the elderly due to the use of bladder and pelvic floor exercises.